2016
DOI: 10.4103/2303-9027.190924
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the viability of hepatocellular carcinoma in the caudate lobe using contrast-enhanced endoscopic ultrasonography after transarterial chemoembolization

Abstract: A 71-year-old female was diagnosed with hepatocellular carcinoma (HCC). The tumor measured 65 mm in diameter and was located in the caudate lobe. Transarterial chemoembolization (TACE) was performed repeatedly; however, a follow-up dynamic computed tomography (CT) scan showed that the tumor remained viable. Thus, TACE was performed using drug-eluting beads that had been preloaded with epirubicin. Contrast-enhanced endoscopic ultrasonography (CE-EUS) was conducted for evaluating the treatment effects. First, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The CH-EUS study of the liver could be divided in three different phases: the arterial phase, starting few seconds after the injection and lasting for 30 s; the portal phase (from 30 to 120 s); and the late, venous phase (after 120 s from injection). [ 4 30 31 ]…”
Section: Methodsmentioning
confidence: 99%
“…The CH-EUS study of the liver could be divided in three different phases: the arterial phase, starting few seconds after the injection and lasting for 30 s; the portal phase (from 30 to 120 s); and the late, venous phase (after 120 s from injection). [ 4 30 31 ]…”
Section: Methodsmentioning
confidence: 99%
“…CEH-EUS has been applied to a lesion in the caudate lobe, which was difficult to assess with percutaneous CE-US. 74…”
Section: Eus Findings Of Liver Lesionsmentioning
confidence: 99%
“…The role of EUS in the diagnosis of liver lesions has not been standardized at this point. EUS‐FNA/FNB is useful in the diagnosis of focal liver lesions, metastatic lesions, early HCC, and evaluation of perihepatic adenopathy 59–85 . Some studies reported that EUS had better accuracy than US, CT and MRI, 65–67 although we need to be careful in extrapolating these older data to current high‐resolution imaging with CT and MRI.…”
Section: Eus For the Diagnosis And Staging Of Liver Lesionsmentioning
confidence: 99%
“…It can dynamically observe tumor vessel perfusion with superior diagnostic performance for residual tumors after transarterial chemoembolization (TACE) compared to CE-CT (sensitivity and accuracy of detecting residual tumor with CE-US 95.6 % and 96.2 % versus CE-CT 76.2 % and 77.7 %, respectively) 29 . For this particular indication, CE-EUS could be of value, with the advantage of better examining the deeper liver lesions not visualized with CE-US 30 . However, this needs further confirmation.…”
Section: Introductionmentioning
confidence: 99%